Analisis Parameter Proses Injection terhadap Konsistensi Kualitas Zinc Die Casting RCA FMEA - Wardiyanto, Anthon Rudi; Aprina, Budi; Ibnu Saputra, Fredy Dwi (Teknologi : Jurnal Ilmiah dan Teknologi, 2025)
The zinc die casting process at PT TST plays a crucial role in producing precision components with high quality standards. However, monthly variations in pass rates indicate inconsistencies in product quality. This condition suggests that injection process parameters such as injection pressure, injection speed, molten temperature, mold temperature, and cycle time are not fully controlled or optimized. Such issues may reduce production efficiency, increase reject rates, and raise rework and polishing costs. Therefore, this study was conducted to analyze the influence of injection process parameters on product quality consistency in zinc die casting using Root Cause Analysis (RCA) and Failure Mode and Effect Analysis (FMEA). The main objectives are to identify the most influential process factors, determine the root causes of defects or declining pass rates, and establish prioritized corrective actions for sustainable improvement. The methodology includes analyzing three months of historical production data (August–October), applying descriptive statistics to measure quality stability, RCA to trace defect causes, and FMEA to assess risk levels through Risk Priority Number (RPN) calculations. Based on production monitoring data over six months after process improvements, total output reached 60,000 units, with 58,817 units passing inspection (98.03%) and 1,183 units rejected (1.97%).